The Impact of Investor Sentiment on Stock Returns in the Indonesian Stock Market During the Period (2001-2022): An Econometric Study - Bagheffar, Abdelkader; Saous , Cheikh (Finance and Business Economies Review, 2023)
The study aims to test the impact of financial investors' sentiment on the returns of IDX Index (JKSE) stocks in the Indonesia Stock Exchange during the period from 2001-2022 using the autoregressive model conditional on the generalized inhomogeneity of variance (GARCH). The study was based on the monthly data of each of the consumer confidence index, which expresses investor sentiment, and the returns of the (JKSE) index. The results showed that there was a statistically significant positive effect of the changes in investor sentiment on the returns of the (JKSE) index during the study period.